Effective Gui test automation: - Li, Kanglin (Sybex, 2004)
This book presents a sensible and highly effective alternative: it teaches you to build and use your own truly automated tool. The procedure you'll learn is suitable for virtually any development environment, and the tool allows you to store your test data and verification standard separately, so you can build it once and use it for other GUIs. Most, if not all, of your work can be done without test scripts, because the tool itself can easily be made to conduct an automatic GUI survey, collect test data, and generate test cases. You’ll spend virtually none of your time playing with the tool or application under test